(untitled) (Rehabilitation and Recreation, 2025)
The objective of this study was to determine which anthropometric variables, such as body mass, height, and limb length, have the greatest impact on swimming velocity over a 50 m freestyle distance inyoung swimmers aged 9–12. The study also aimed to assess whether differences in results were statistically significant based on the age and gender of the athletes.Materials and methods. The research was conducted on a group of 100 swimmers (50 girls and 50 boys) from a Trójmiasto swimming club, divided into four age groups (9, 10, 11, 12 years). All participants trained 6 times a week using the Total Immersion method. The first stage involved collecting anthropometric measurements: body mass (kg), body height (cm), and the length of the upper and lower limbs (cm). In the second stage, swimming velocity was measured over a 50 m freestyle distance. The collected data was subjected to statistical analysis using Student’s t-test, the Kruskal-Wallis test, and Pearson’s correlation coefficient, with a significance level set at p < 0.05.Results. No statistically significant differences were found in anthropometric characteristics (bodymass, height, limb length) or swimming velocity between girls and boys within the same age groups.However, a statistically highly significant (p < 0.001) relationship was demonstrated between swimming velocity and the age of the athletes – the older the swimmers, the shorter the time it took to complete the distance. A statistically highly significant (p < 0.001) negative correlation was also found between swimming velocity and body mass, height, and limb length. This means that greater body mass, height, and longer limbs resulted in faster swimming. Exceptions were noted: in the 10-year-old group, the correlation between body mass and velocity was positive (p < 0.05), and in the 11-year-old group, no significant relationship was found between body height and velocity.Conclusions. Body mass, height, and limb length have a significant impact on the swimming velocity of young athletes. Gender is not a decisive factor in performance within this age range. The identified correlationsprovide valuable insights for coaches, enabling them to optimize the training process and adopt an individualized approach to athlete development, particularly in the context of dynamic somatic changes during puberty.